From stem cells protection to skin microbiota balance: Orobanche rapum extract, a new natural strategy. (28th November 2018) - Meunier, Marie; Scandolera, Amandine; Chapuis, Emilie; Lambert, Carole; Jarrin, Cyrille; Robe, Patrick; Chajra, Hanane; Auriol, Daniel; Reynaud, Romain
Summary: Background: Healthy skin is a delicate balance between skin renewal and microbiota homeostasis, and its imbalance promotes premature aging and dermatological disorders. Skin stem cells are key actors in this process but their sensitivity to aging and external stressors such as UV reduces the skin renewal power. The skin microbiota has been recently described as active in the healthy skin, and its imbalance could trigger some disorders. Aims: We hypothesized that reactivation of stem cells and maintenance of microbiota could be a disruptive strategy for younger and healthier skin. We thus developed a new plant extract that restores the entire skin renewal process by sequential activation from stem cells stimulation to microbiota protection. Methods: We studied stem cells comportment in the presence of Orobanche rapum extract by survivin immunocytochemistry and caspases 3 and 9 dosages. We also analyzed epidermal differentiation markers by immunohistochemistry and lipids organization by GC/MS At the clinical level, we investigated the impact of O. rapum extract on microbiota and on skin aspect. Results: We demonstrated an active protection of skin stem cells through the maintenance of their clone‐forming capacity and resistance to UV through the overexpression of survivin coupled to caspases inhibition. Furthermore, we showed the restoration of epidermal differentiation markers and ceramide biosynthesis favorable to orthorhombic organization. Clinical studies, including microbiota analysis, showed an active skin surface renewal coupled with microbiota protection. Conclusion: We evidenced that our active ingredient is able to stimulate skin rejuvenation while protecting the cutaneous microbiota, creating healthier skin and thereby beauty.